Answer:
5x^2 -3x +9
Step-by-step explanation:
To subtract, line up the common terms. I add a 0 term to keep the terms in line.
5x^2 + 0x +7
- (0x^2 +3x- 2 )
------------------------
Distribute the negative sign.
5x^2 + 0x +7
- 0x^2 -3x + 2
------------------------
5x^2 -3x +9
Answer:
24.56
Step-by-step explanation:
1.14x-5+5=23+5
1.14x=28
x is roughly equal to 24.56.
Hope this helps!
Sorry I needed points for an important quiz
We can’t measure these. How long is each of them
Answer:
x = 2, x = 4
Step-by-step explanation:
The equation y = 10 - 9x is a linear equation and the value of either y or x can be found by substituting the given values of either y or x.
given that y = -8, and substituting this into equation y = 10 - 9x,
we have, -8 = 10 - 9x
10 + 8 = 9x
9x = 18; dividing both sides by 9
x = 2
given that y = -26, and substituting this into equation y = 10 - 9x,
we have, -26 = 10 - 9x
10 + 26 = 9x
9x = 36; dividing both sides by 9
x = 4